Ultrastructural study of morphological changes in Schistosoma mansoni after in vitro exposure to the monoterpene rotundifolone - Matos-Rocha,Thiago José (2017)
ABSTRACT INTRODUCTION: Schistosomiasis, a parasitic disease caused by trematode flatworms of the genus Schistosoma, affects more than 200 million people worldwide, and its control is dependent on a single drug, praziquantel. Here, we report the in vitro effect of rotundifolone, a monoterpene isolated from Mentha x villosa (Lamiaceae), on Schistosoma mansoni adult worms. METHODS: The in vitro effect of rotundifolone on adult Schistosoma mansoni was evaluated by analysis of behavior and mortality and through a scanning electron microscopic analysis of ultrastructural changes in the tegument of the worms. RESULTS: At concentrations of 3.54 and 7.09μg/mL-1 rotundifolone, no worm mortality was observed at any of the sampling intervals. A minor reduction in movement of the tail, suckers, and gynecophoral canal membrane was observed after 96 h of exposure to 7.09μg/mL-1 rotundifolone. At 70.96μg/mL-1, a lack of movement was observed from 72h onwards and all worms were deemed dead; similar effects were observed at 48h with 177.4μg/mL-1, and at 24h with 354.8μg/mL-1 and 700.96μg/mL-1. Rotundifolone also caused death of all parasites and separation of coupled pairs into individual males and females after 24h at 354.8μg/mL-1. CONCLUSIONS: The main changes in the tegument induced by the different ROT treatments were: after 24h incubation, bubble lesions spread over the entire body and loss of tubercles occurred in some regions of the ventral region.